Response surface methodology based on central composite design as a chemometric tool for optimizing dispersive liquid–liquid microextraction for determining ultra-trace amounts of zinc in oil and water samples. Issue 25 (15th June 2016) - Khazaeli, Elaheh; Haddadi, Hedayat; Zargar, Behrooz; Hatamie, Amir
Abstract : The reliable and rapid dispersive liquid–liquid microextraction method for extraction of ultra-trace Zn 2+ levels. Abstract : The reliable and rapid dispersive liquid–liquid microextraction (DLLME) was applied to highly selective preconcentration and extraction of ultra-trace Zn 2+ levels as a prior step to its determination by graphite furnace atomic absorption spectrometry (GFAAS). In this method, N, N -phenylenebis (salicylideaminato) (L) was used as a Zn 2+ selective complexing agent. A mixture containing a dispersing solvent (methanol), extraction solvent (chloroform), and proper levels of the chelating agent was rapidly injected into the 5 mL aqueous sample containing 2.5% (w/v) sodium chloride and Zn 2+, which resulted in a cloudy solution. After 5 min of centrifuging at 5500 rpm, the fine droplets of extraction solvent were sedimented at the bottom of the conical test tube. The variables of interest in the DLLME method, such as extraction and dispersion solvent types and volumes, sample solution pH, extraction time, chelating agent concentration, and ionic strength, were investigated and optimized using a chemometrics approach. Then, after the preliminary experiment, the factors presenting significant positive effects on the analytical response (pH, salt effect, extraction solvent, and ligand concentration) were considered in a further response surface methodology based on central composite design to optimize the operational conditions for DLLME. It was found that extraction time and common interfering ions had no significant effect on the extraction recovery. Under the selected conditions, the linear range was 0.2–100 ng mL −1 and limit of detection was 0.05 ng mL −1 for most of the analytes. The relative standard deviation (R.S.D) for 2 ng mL −1 Zn 2+ was 4.87% ( n = 15) and the enrichment factor was 167 from 5 mL of the aqueous sample. In the optimum conditions, the present method was successfully applied to the preconcentration and Zn 2+ determination in different natural oil and water samples.